2019
DOI: 10.1111/cpf.12615
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in fluid retention – towards a mutual concept

Abstract: Fluid retention is a common and challenging condition in daily clinical practice. The normal fluid homoeostasis in the human body is based on accurately counter-balanced physiological mechanisms. When compromised fluid retention occurs and is seen in pathophysiologically different conditions such as liver cirrhosis, heart and kidney failure, and in preeclampsia. These conditions may share pathophysiological mechanisms such as functional arterial underfilling, which seems to be a mutual element in cirrhosis, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…As normal pregnancy is associated with fluid and sodium retention [ 51 ], the attention around the possible role of EDLF in pregnancy arose after their discovery [ 52 ]. In 1984, two research teams found an endogenous factor that cross-reacted with digoxin antibodies in the serum of pregnant women, and increased levels of this factor were associated with hypertensive disorders of pregnancy [ 53 , 54 ].…”
Section: Endogenous Digitalis-like Factors (Edlf)mentioning
confidence: 99%
“…As normal pregnancy is associated with fluid and sodium retention [ 51 ], the attention around the possible role of EDLF in pregnancy arose after their discovery [ 52 ]. In 1984, two research teams found an endogenous factor that cross-reacted with digoxin antibodies in the serum of pregnant women, and increased levels of this factor were associated with hypertensive disorders of pregnancy [ 53 , 54 ].…”
Section: Endogenous Digitalis-like Factors (Edlf)mentioning
confidence: 99%
“…Penurunan laju filtrasi glomerulus (GFR) menyebabkan retensi Na dan H2O dalam tubuh sehingga menyebabkan penumpukan cairan. (Mottelson et al, 2020) Fungsi utama ginjal untuk mempertahankan homeostatik yaitu mengatur volume cairan, asam basa, keseimbangan osmotik, eksresi sisa metabolism, sistem pengaturan hormonal serta metabolisme. Ketika terjadi kegagalan pada fungsi ginjal, tubuh tidak dapat mempertahankan metabolisme serta keseimbangan cairan & elektrolit, maka terjadi penumpukan sisa-sisa metabolik (toksik uremik) dalam darah serta penumpukan cairan (Galuh et al, 2020).…”
Section: Pendahuluanunclassified
“…As a normal pregnancy is accompanied by fluid retention and a positive sodium balance in the body [15], interest in the possible role of CS in pregnancy arose shortly after their discovery. Graves et al showed that the level of digoxin-like immunoreactivity increases moderately in a healthy pregnancy and rises significantly with gestational hypertension [16].…”
Section: Cardiotonic Steroids Pregnancy and Preeclampsiamentioning
confidence: 99%